PENGARUH PINJAMAN DANA BERGULIR TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT MISKIN DI KOTA MAKASSAR - Urbanus Uma Leu (IAIN Ambon, 2017)
Poor economic communities need empowerment so that their economies can increase. In this connection this paper aims to reveal and analyze (1) the conditions for implementing the P2KP revolving fund loan in Tamalate District; (2) the effect of revolving fund loans on increasing the income of the poor. Data was collected through documentation techniques, interviews, and questionnaires. The results of the study show that the recipients / beneficiaries of the Revolving Fund National Urban Community Empowerment Program (PNPM) program are greatly assisted in the development of businesses that have been managed; and the Revolving Fund Program run by the Community Self-Help Agency in Tamalate District is quite effective in supporting business capital. Keywords: revolving funds, income of the poor